KUALITAS PELAYANAN PT KERETA API INDONESIA Studi Kasus : Kualitas Pelayanan Kereta Api Ekonomi AC Gajah Wong Relasi Yogyakarta â Jakarta - , AHMAD WASKHITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The railway system has become part of Indonesian society since the Dutch colonial era to transport passengers and farm commodities. It had been connecting and developing many areas, especially in Java and Sumatera. Because of the effectiveness of this vehicle, the railway passenger transport also experiencing innovation. One of the innovation is to operate new rail called Gajahwong, which is the commercial economy class train with air conditioner systems. The train route is Jakarta - Yogyakarta or otherwise. Gajahwong is operated to achieve the minimum standards for public transport service by railways created by the Ministry of Transportation through the ministrial regulation (Peraturan Menteri No. 9 tahun 2011 tentang Standar Pelayanan Minimal untuk Angkutan Orang Dengan Kereta Api) especially concerning the air conditioning facilities. This train included in commercial services of PT KAI. This research reveals how the quality of services provided by PT KAI Daop VI Yogyakarta to the railway passenger trains operating through Gajahwong . the result showed that Gajahwong considered good enough by the consumers, with some advantages and disadvantages. Reliability of trains that never experienced a fatal accident be good value in this service. In addition, the timing is very rarely crosses the tolerance level of SPM also adds positive value . However, the problem of facilities like train seats are not comfortable, no disabled facilities as required by minimum standards regulation, and the expensive price, had to be considered by PT KAI Daop VI Yogyakarta. Evaluation and improvement must be performed, so that better service can be held by Gajahwong.